Neural Recovery Function of the Auditory Nerve in Cochlear Implant Surgery: Comparison between Prelingual and Postlingual Patients - Carvalho, Bettina; Wiemes, Gislaine Richter Minhoto; Patrial Netto, Luiz; Hamerschmidt, Rogerio (International Archives of Otorhinolaryngology, 2020)
Introduction Cochlear implants (CIs) enable objective measures of the neural function in implanted patients through the measurements of the neural response telemetry (NRT) and of the Auditory nerve Recovery Function (REC). These measurements help in programming the speech processor and understanding the auditory system.Objective To compare the NRT and the REC in prelingual and postlingual implanted patients.Methods An observational, descriptive and prospective study was carried out. The NRT and the REC (through the T0, A, and tau parameters) were evaluated in individuals submitted to CI surgery, who were divided into two groups: prelingual and postlingual patients.Results In total, 46 patients were evaluated. Data analysis showed no statistically significant difference between the NRT measurements and the T0, A, and Tau of the REC in the comparison between the two groups, except for the NRT in the basal cochlear region.Conclusion There was no statistically significant difference in the REC in pre- and postlingual patients.
Keywords: cochlear implants; prelingual hearing loss; postlingual hearing loss; neural response telemetry